GANGGUAN BERBAHASA PADA TOKOH SHAHIDA DALAM FILM “BAJRANGI BHAIJAAN” (KAJIAN PSIKOLINGUISTIK) - Alya Maulidia Zahra (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
This study aims to determine the language disorders of Shahida's character in the film "Bajrangi Bhaijaan". The background of this research focuses on the theory of language disorders in psycholinguistics. The research was conducted by listening to the film and then noting important things related to language disorders that will be carried out regarding the speech impaired in the film "Bajrangi Bhaijaan". It can be seen that in the film "Bajrangi Bhaijaan" tells the story of a little boy named Shahida who can't speak, so at that time he couldn't scream for help and could only wait for someone else to help him. As a result of the incident, the elders and community leaders there also consulted and advised Shahida's parents to take her to a holy place in India. The goal is to treat Shahida so she can talk like other children. However, the journey did not go smoothly. There are many obstacles to be overcome. Thus, the character Shahida has difficulty communicating with other people.